Hospitalizations and mortality due to falls in the elderly, piauí-brazil, 2014 to 2021 (Revista Contexto & Saúde, 2025)
This study aimed to analyze the trend of hospitalizations and mortality due to falls among the elderly in Piauí between 2014 and 2021. This is an ecological, time-series study using data on hospitalizations and deaths due to falls during the period from 2014 to 2021 in Piauí. Data were collected from the Hospital Information System of the Brazilian Unified Health System (SUS). To analyze trends, the Prais-Winsten linear regression model was applied, with autocorrelation assessed using the Durbin-Watson test. A total of 16,048 hospitalizations and 516 deaths due to falls among elderly people were analyzed by sex, age group, and health region. A stationary trend in hospitalization and mortality rates was observed according to the variables used. The need to improve and expand fall prevention measures and programs for the elderly is reinforced.
Keywords: Accidental falls; Elderly; Mortality; Hospitalization; Time series studies